Classification of the Cardiac Arrhythmia Using Combined Feature Selection Algorithms - Tunç, Murat; Cangöz, Gülnur Begüm (Fırat Üniversitesi, 2024)
The prediction of heart disease has gained great importance in recent years. Efficient monitoring of cardiac patients can save tremendous number of lives. This paper presents a method for classification and prediction of electrocardiogram data obtained from 452 patients representing the risk of cardiac arrhythmia. The aim of the study is to select highly related features with arrhythmia risk by using three different feature selection algorithms. In addition, various machine learning models are utilized for the classification task such as k-Nearest Neighbors (k-NN), Support Vector Machines (SVM) and Decision Tree (DT). The experimental results show that combination of a purposed feature selection method which later is called “Matched Selection” using SVM classifier outperforms other combinations and have an accuracy of 81.27% while k-NN and DT classifiers have an accuracy of 69.66% and 73.50% respectively. The study, in which detailed analyses are presented comparatively, is promising for the future studies.

Kalp hastalıklarının önceden tahmin edilmesi son yıllarda büyük önem kazanmıştır. Kalp hastalarının etkin bir şekilde izlenmesi, sayısız hayatın kurtarılmasını sağlayabilir. Bu makale, kardiyak aritmi riski taşıyan 452 hastadan elde edilen elektrokardiyogram verilerinin sınıflandırılması ve hastalıkların tahmin edilmesi için yenilikçi bir yöntem sunmaktadır. Bu çalışmanın ana hedefi, üç farklı öznitelik seçme algoritmasını kullanarak aritmi riski ile yüksek derecede bağlılık gösteren özniteliklerin seçilmesidir. Ayrıca, sınıflandırma görevi için En yakın komşular algoritması(k-NN), Destek Vektör Makineleri (SVM) ve Karar Ağaçları (DT) gibi çeşitli makine öğrenimi modelleri kullanılmaktadır. Deneysel sonuçlar, Destek Vektör Makineleri (SVM) sınıflandırıcısı ve "Eşleştirilmiş Seçim" öznitelik seçim yönteminin diğer kombinasyonları geride bıraktığını göstermektedir. Bu kombinasyon %81.27 doğruluk oranına sahipken, k-NN ve DT sınıflandırıcılarının doğruluk oranları sırasıyla %69.66 ve %73.50'dir. "Detaylı analizlerin karşılaştırmalı olarak sunulduğu bu çalışma, gelecekteki araştırmalar için umut vadetmektedir.
Öznitelik Seçim Algoritmalarının Kombinasyonu ile Kardiyak Aritminin Sınıflandırılması
Keywords: Reinforcement Learning; Takviyeli Öğrenme